Object oriented programming based MATLAB toolbox to solve transient quasi-harmonic equation using finite element methods - Jayesh, S W; Jeyakarthikeyan, P V; Yogeshwaran, R (IOP conference series. Materials Science and Engineering, 2018)
Many heat conduction problems encountered in engineering applications are time intensive they are dependent on unsteady state variables. In many situations, temperature varies with respect to time function, for which a solution needs to be found. In this research paper, a 2D transient Qausi-harmonic equation is solved using Finite element method. In engineering applications, many engineering problems are governed by this Qausi-harmonic equation. The main aim of this analysis is to determine the variation of the temperature as a function of time by finding element conductivity matrix using standard Gauss quadrature numerical integration method as it is both accurate and efficient. The obtained results of MATLAB coding are verified with ANSYS with examples. Toolbox is created in MATLAB using Object Oriented Programming language for this analysis. The template of this toolbox is also added in this paper.